Cough as an adverse reaction of angiotensin converting enzyme inhibitory - Woroń, Jarosław; Korbut, Ryszard (Przewodnik Lekarza/Guide for GPs, 2005)
Cough is common adverse reactions during ACE inhibitors therapy. In pathogenesis of drug-indeced cough very important are bradykinin, prostaglandins and nitric oxide. Imidapril is a novel ACE inhibitor indicated in hypertension with very low incidence of cough.